Comparative performance analyses of commercially available products for salivary collection and nucleic acid processing in the newborn. (17th November 2015) - Maron, JL; Johnson, KL
Abstract : Analysis of saliva for clinical monitoring and biomarker detection holds great promise for improving health care. Commercially available assays are not intended for use with neonates, however, and collection and processing of saliva for subsequent transcriptomic analysis presents unique challenges in this population. We compared RNA yield, quality, stability and RT-qPCR performance for two commonly used commercial systems: the Qiagen RNeasy Protect Saliva Mini Kit ® and the DNA Genotek OrageneRNA ® assay. Two 10 μl saliva samples were collected from ten newborns and stabilized for each assay. Total RNA was extracted following incubation for 3, 10, 15 or 20 days. Total RNA extracted from each assay was analyzed for integrity, quality and quantity using the Agilent BioAnalyzer 2100. RT-qPCR was performed for the reference gene, GAPDH, to assess subsequent performance of the extracted RNA. Although the DNA Genotek extraction protocol required nearly twice the time of the Qiagen protocol, RNA integrity did not differ between the kits. RNA concentration using the DNA Genotek assay, however, was 3, 264 pg/μl (range: 262 − 10, 336 pg/μl) compared to 822.4 pg/μl (range: 0 − 1, 856 pg/μl) for the Qiagen protocol. Linear regression analysis showed a stronger correlation between the threshold cycle and RNA concentration using DNA Genotek (r 2 = 0.356) compared to Qiagen (r 2 = 0.0331). Our results suggest that although the Qiagen assay may reduce overall extraction time, RNA yield and performance in subsequent transcriptomic analysis is more robust using the DNA Genotek assay.